Fostering Trust In Collaborative: Building Child-Friendly Cities in Emerging Industrial Landscapes - Tobirin tobirin; Sunee Hongwiset; Slamet Rosyadi; Siti Kunarti; Darmanto Sahat (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2023)
This article examines the reconstruction of stakeholder confidence in the collaborative governance process for the sustainability of child-friendly cities in new industrial communities. Research problems are due to the implications of the growth of new industrial societies, differences and conflicts of interest between stakeholders, child growth and development problems, high stunting, juvenile delinquency, street children, and parenting patterns that are not by needs. This study aims to analyze the reconstruction of stakeholder trust in creating awareness and shared commitment to collaborative governance processes to realize the sustainability of child-friendly cities. The research method is qualitative, research data is collected through in-depth interviews and focus group discussions (FGD). The results of the study show that collaborative governance processes are faced with different interest gaps that result in a lack of trust and commitment to realizing a child-friendly city. A joint forum among stakeholders in the child-friendliness campaign efforts has been organized but shows no signs of effectiveness. The lack of synergy between local governments and industry players is present, therefore efforts to rebuild trust in realizing the sustainability of a child-friendly environment need to be optimized through communication, openness, social responsibility, and supervision of local governments.